“POR HOJE É SÓ HOLLYWOOD”: ANÁLISE A RESPEITO DA MORTE NO MÉXICO E NO HAITI E O PODER DOS FILMES NA DISSEMINAÇÃO DA CULTURA - Freire Guimarães, Beatriz; Lacerda Lima Filho , Sebastião; de Moraes Filho, Manoel Odorico; S. Macedo , Danielle; Stéphane Laurent, Emmanuel (Revista de Ciências Humanas Caeté, 2025)
Conceptions about the phenomenon of death in different societies are deeply influenced by religious and cultural factors. Although there are marked differences in the methods and practices adopted, many rituals share similar foundations, which aim to preserve the memory and identity of the respective peoples. In Latin America, specifically in Mexico and Haiti, both Haitians and Mexicans have a conception of death that emphasizes the importance of celebration, rituals and spiritual beliefs. However, due to religious factors and, above all, the power of the media, the perception of death in Haiti, associated with Voodoo, is often stigmatized outside the country, generating fear and prejudice, largely due to the macabre image disseminated by Hollywood films. On the other hand, the representations disseminated about the festive and colorful celebration of death in Mexico exert a fascination that attracts visitors to the country. Thus, the purpose of this article is to address, in a didactic way, the differences and similarities in the way death is perceived in these countries, providing basic information about the religious culture of these peoples. The project is the result of scientific collaboration and the unfolding of a larger research project entitled "Vodou Project: studies in Cognitive Anthropology, Ethnobotany and Traditional Medicine on Isla Hispaniola: Caribbean Sea".